Derivados hidroxicinamicos para la discriminacion de genotipos de cafe - Guerrero A, G.=700 1 Suarez, M.; Moreno Ruiz, G.
(Es)
ilus., 31 ref.
Keywords: RUBIACEAE; COFFEA ARABICA; VARIEDADES; METODOS ESTADISTICOS; CROMATOGRAFIA; HPLC; COLOMBIA; DERIVADOS HIDROXICINAMICOS